Zakat as a Fiscal Instrument and Tax Revenue Moderation on Indonesia's Economic Growth - Ilma Aulia Sabarita; Anton Bawono (Program Studi Manajemen Zakat dan Wakaf, 2026)
National economic growth is affected by both traditional fiscal policies, like taxation, and Islamic fiscal tools, such as zakat. This study seeks to examine the function of zakat as an Islamic financial tool in Indonesia's economic development, utilizing tax revenue as a moderating variable. Secondary sources for this research were acquired from the National Zakat Agency (BAZNAS), the Directorate General of Taxes (DGT), and the Central Statistics Agency (BPS) covering the period from 2001 to 2024. The analytical approach employed is Moderated Regression Analysis (MRA) utilizing STATA software to examine the impact of the interplay between zakat and tax revenue on economic growth. The findings of this study indicate that zakat exerts a negative and significant influence, whereas tax revenue can enhance the synergy between zakat and economic growth. This indicates the merger of conventional and Islamic fiscal systems to broaden the state's revenue base and enhance productive economic activity. These findings affirm that zakat serves as a supplementary tool for fiscal policies aimed at equity and a healthy econom.